A comparison of ocular melanocyte and uveal melanoma cell invasion and the implication of α1β1, α4β1 and α6β1 integrins. Issue 6 (1st June 2001) - Elshaw, Shona R; Sisley, Karen; Cross, Neil; Murray, Anna K; MacNeil, Shiela M; Wagner, Mark; Nichols, Carmel E; Rennie, Ian G
Abstract : BACKGROUND/AIMS: Posterior uveal melanoma is the most common intraocular tumour in adults, responsible for the death of approximately 35% of patients. Hepatic metastases are most frequent, and once diagnosed survival is usually less than 1 year. The β1 family of integrins, αvβ3 and MMP-2 and MMP-9 have been implicated in the metastasis of several types of tumour. To study their involvement in uveal melanoma we analysed the expression of the β1 integrins, αvβ3, MMP-2, and MMP-9 in 10 primary posterior uveal melanomas, and correlated expression with invasive potential in vitro. Comparable studies were undertaken on cultures of melanocytes. METHODS: Expression of integrins was studied by immunohistochemistry, secretion of MMP-2 and MMP-9 by zymography, and the invasive potential was assessed using a transwell model. RESULTS: MMP-2 was secreted by all uveal melanomas and seven of 10 secreted MMP-9. Among uveal melanoma, invasion levels of 4–25% were observed and the major integrins expressed were α1β1, α2β1, α3β1, α5β1, and avβ3. Melanocytes did not express α1β1, α4β1, and α6β1. CONCLUSION: The laminin binding α6β1 integrin was not expressed by either melanocytes or tumours with spindle morphology, which are considered to have a better prognosis. It is possible that expression of the α6β1 integrin may prove useful as a prognostic indicator.